A Conceptual Framework to Integrate Biodiversity, Ecosystem Function, and Ecosystem Service Models. (1st September 2022) - Weiskopf, Sarah R; Myers, Bonnie J E; Arce-Plata, Maria Isabel; Blanchard, Julia L; Ferrier, Simon; Fulton, Elizabeth A; Harfoot, Mike; Isbell, Forest; Johnson, Justin A; Mori, Akira S; Weng, Ensheng; HarmáCˇková, Zuzana V; et al.
Abstract: Global biodiversity and ecosystem service models typically operate independently. Ecosystem service projections may therefore be overly optimistic because they do not always account for the role of biodiversity in maintaining ecological functions. We review models used in recent global model intercomparison projects and develop a novel model integration framework to more fully account for the role of biodiversity in ecosystem function, a key gap for linking biodiversity changes to ecosystem services. We propose two integration pathways. The first uses empirical data on biodiversity–ecosystem function relationships to bridge biodiversity and ecosystem function models and could currently be implemented globally for systems and taxa with sufficient data. We also propose a trait-based approach involving greater incorporation of biodiversity into ecosystem function models. Pursuing both approaches will provide greater insight into biodiversity and ecosystem services projections. Integrating biodiversity, ecosystem function, and ecosystem service modeling will enhance policy development to meet global sustainability goals.